2020
DOI: 10.1038/s41598-020-62479-w
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Scoring Method for Predicting the Low Risk of Persistent Acute Kidney Injury in Critically Ill Adult Patients

Abstract: The renal angina index has been proposed to identify patients at high risk of persistent AKI, based on slight changes in serum creatinine and patient conditions. However, a concise scoring method has only been proposed for pediatric patients, and not for adult patients yet. Here, we developed and validated a concise scoring method using data on patients admitted to ICUs in 21 Japanese hospitals from 2012 to 2014. We randomly assigned to either discovery or validation cohorts, identified the factors significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 22 publications
1
27
1
4
Order By: Relevance
“…A growing body of evidence suggests that duration of AKI or renal recovery is associated with outcomes in critically ill septic patients 2 , 7 , 8 , 33 , 34 . Several clinical tools, including urinary indices 10 12 , imaging techniques 13 , 17 , prediction models 35 , 36 , and biomarkers 14 17 , were investigated in previous studies to predict renal recovery or its surrogate, namely progression to severe AKI. Nevertheless, they were found to be poorly effective or have not been validated in patients with sepsis 9 .…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that duration of AKI or renal recovery is associated with outcomes in critically ill septic patients 2 , 7 , 8 , 33 , 34 . Several clinical tools, including urinary indices 10 12 , imaging techniques 13 , 17 , prediction models 35 , 36 , and biomarkers 14 17 , were investigated in previous studies to predict renal recovery or its surrogate, namely progression to severe AKI. Nevertheless, they were found to be poorly effective or have not been validated in patients with sepsis 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have predicted AKI prognosis with effective predictions to support decision-making. Several clinical tools, including prediction models [23,24], urinary indices [25,26], novel biomarkers [27,28], and imaging techniques [29] were canvassed in previous studies to predict renal recovery, namely progression to severe AKI. For example, a recent study enrolling 8,320 critical patients with AKI found a poor performance of SOFA and △Cr for predicting persistent AKI, with the AUC of 0.69 (95%CI 0.66-0.71) and 0.74 (95%CI 0.71-0.77), respectively [23].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical tools, including prediction models [23,24], urinary indices [25,26], novel biomarkers [27,28], and imaging techniques [29] were canvassed in previous studies to predict renal recovery, namely progression to severe AKI. For example, a recent study enrolling 8,320 critical patients with AKI found a poor performance of SOFA and △Cr for predicting persistent AKI, with the AUC of 0.69 (95%CI 0.66-0.71) and 0.74 (95%CI 0.71-0.77), respectively [23]. Furthermore, the renal angina index has been proposed to detect critically ill children at high risk of persistent AKI, validated as an effective screening tool.…”
Section: Discussionmentioning
confidence: 99%
“…A pesar de la escasa información disponible sobre el comportamiento de la LRA en República Dominicana 12,13 , la implementación del IAR posibilita la detección oportuna de LRA y por añadidura los beneficios potenciales de esta acción: control en el uso de recursos (días de hospitalización, secuelas, costos de atención, etc.) 4,14 . -Este esfuerzo se enfoca en responder a las necesidades de países de Latinoamérica, en donde se precisa aprovechar al máximo los recursos disponibles.…”
Section: Recomendacionesunclassified
“…Nuestra región se caracteriza por gran desigualdad social e inequitativa repartición de recursos 13 , afectando a los servicios de salud y puede constituir una barrera para la introducción de nuevas tecnologías tanto para diagnóstico como tratamiento. -Consideramos al IAR descrito por Matsuura et al 14 como el sistema de estratificación de riesgo para LRA de mayor potencial para su implementación dentro de las UCI polivalentes dentro de República Dominicana. C: 8 de 8 presentes (100%); GE moderada; GR: fuerte.…”
Section: Recomendacionesunclassified